Programmable, Expressive, Scalable, and Agile Service Function Chaining for Edge Data Centers - Dominicini, Cristina Klippel; Martinello, Magnos; Ribeiro, Moisés Renato Nunes (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2020)
Edge computing transfers processing power from large remote data centers (DCs) to distributed DCs at the edge of the network. This shift requires the ability to provide network functions virtualization (NFV) solutions that can efficiently manage and combine a large number of dynamic services in a resource-constrained DC. However, the routing mechanisms of traditional data center networks are not adequate for the dynamic composition of these services, because they are complex, rigid, subject to large delays in the propagation of control information, and limited by the size of switches' routing tables. In addition, traditional service function chaining (SFC) solutions in the service overlay are often decoupled from routing decisions in the network underlay, and restrict path selection options by traffic engineering. In this way, the NFV orchestrator cannot explore the full capacity of the network to provide composite services. To tackle these issues, this thesis investigated a programmable, expressive, scalable, and agile SFC proposal that allows dynamic and efficient orchestration of the network infrastructure of edge DCs with commodity network equipment. The proposal exploits virtualization and programmability technologies of DC networks, server-centric DCs, fabric networks, and a source routing mechanism based on the residue number system (RNS). As proof-of-concept, we developed prototypes with production DC technologies, such as OpenFlow, OpenStack, Open vSwitch and P4. The results of functional and performance tests showed that the proposed SFC scheme provides mechanisms to the NFV orchestrator that allow traffic engineering to make optimized decisions in the selection of network paths. This thesis also paves the way for exploring RNS-based source routing properties in SFC schemes, which can provide features such as fast failure reaction and forwarding without packet rewrite. In a broader analysis, the student published 22 papers in journals and conferences, contributed to funding initiatives, worked on international and national research projects, supervised undergraduate students, and leaded initiatives with innovation impacts.